Efficiency of wind power production and its determinants - Simone Pieralli; Matthias Ritter; Martin Odening (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
This article examines the efficiency of wind energy production. We quantify production losses in four wind parks across Germany for 19 wind turbines with non-convex efficiency analysis. In a second stage regression, we adapt the linear regression results of Kneip, Simar, Wilson (2014) to explain electricity losses by means of a bias-corrected truncated regression. Our results show that electricity losses amount to 27% of the maximal producible electricity. These losses can be mainly traced back to changing wind conditions while only 6 % are caused by turbine errors.
Keywords: D20; D21; Q42; 330; wind energy; efficiency; free disposal hull; bias correction